2016
DOI: 10.2147/opth.s100280
|View full text |Cite
|
Sign up to set email alerts
|

Microbiology of primary acquired nasolacrimal duct obstruction: simple epiphora, acute dacryocystitis, and chronic dacryocystitis

Abstract: PurposeThe aim of this study was to determine the microbiology of primary acquired nasolacrimal duct obstruction (PANDO) and its antimicrobial susceptibilities.MethodsNinety-three patients (100 eyes) diagnosed with PANDO, categorized as acute, chronic dacryocystitis, or simple epiphora, were prospectively enrolled. Lacrimal sac contents were cultured for aerobic and anaerobic bacteria and fungi. Cultured organisms were identified, and antimicrobial susceptibility testing was performed for aerobic bacteria.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 14 publications
5
29
0
Order By: Relevance
“…The clinical importance of microbial causes of CANDO and pattern of drug resistance is widely recognized as a key part of the treatment strategy in these patients. Similar to the results of previous studies, the authors found that in patients with CANDO, a great variety of bacterial pathogens can be isolated (2-4). Shahrakiet et al found that 46.7% of all samples were negative – normal, and only 6.7% were marked with gram positive bacteria.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…The clinical importance of microbial causes of CANDO and pattern of drug resistance is widely recognized as a key part of the treatment strategy in these patients. Similar to the results of previous studies, the authors found that in patients with CANDO, a great variety of bacterial pathogens can be isolated (2-4). Shahrakiet et al found that 46.7% of all samples were negative – normal, and only 6.7% were marked with gram positive bacteria.…”
supporting
confidence: 87%
“…In the results from previous studies, negative cultures were found in 17.8% of patients in Thailand (4), 15.6% in Nepal (3) and only 10% in United States (5). Additionally, in most of previous studies gram positive bacteria were the most predominant in culture positive specimens, from 64.9% to 78.5% (2-4). Thus, Pornpanich et al found that in patients with longer duration of the CANDO symptoms, gram negative cultures become more common (2).…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Bacterial cultures from the purulent discharge (sampled at the sac, fistula or abscess surgical incision) are commonly performed [3]; both in children and in adults, the most frequently isolated germ is methicillin-sensitive Staphylococcus aureus, followed by Streptococcus pneumoniae. Gram negative species can be detected in culture positive acute dacryocystitis too [1,6].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic dacryocystitis is one of the most common causes of epiphora due to insufficient drainage. The insufficient drainage is due to either congenital causes like punctal atresia, diverticulum or fistula from sac to nose or cheek, Nasolacrimal Duct Obstruction (NLD), agenesis or acquired causes 1 processes, chronic disease, dacryoliths, allergy, systemic chemotherapeutic agents, postherpetic infection (Herpes simplex, varicella zoster), bacterial infection (Actinomyces, Chlamydia), Wegener granulomatosis, sarcoidosis, hay fever, atopy, etc.…”
Section: Introductionmentioning
confidence: 99%